Consortium of Probiotics Attenuates Colonization of Clostridioides difficile - Li, Xianping; Chu, Qiongfang; Huang, Yuanming; Xiao, Yuchun; Song, Liqiong; Zhu, Siyi; Kang, Ying; Lu, Shan; Xu, Jianguo; Ren, Zhihong (Frontiers in Microbiology, 2019)
Clostridioides difficile infection (CDI) is increasing morbidity and mortality rates globally. Fecal microbiota transplantation (FMT), an effective therapy for eliminating Clostridioides difficile (C. difficile), cannot be used extensive due to a range of challenges. Probiotics thus constitutes a promising alternative therapy. In our study, we evaluated the effect of consortium of probiotics including five Lactobacilli strains and two Bifidobacterium strains on the colonization of toxigenic BI/NAP1/027 C. difficile in a mouse model. The results of 16S rRNA sequencing and targeted metabolomics showed the consortium of probiotics effectively decreased the colonization of C. difficile, changed the α- and β-diversity of the gut microbiota, decreased the primary bile acids, and increased the secondary bile acids. Spearman’s correlation showed that some of the OTUs such as Akkermansia, Bacteroides, Blautia et al were positively correlated with C. difficile numbers and the primary bile acids, and negatively correlated with the secondary bile acids. However, some of the OTUs, such as Butyricicoccus, Ruminococcus, and Rikenellaceae, were negatively correlated with C. difficile copies and the primary bile acids, and positively correlated with the secondary bile acids. In summary, the consortium of probiotics effectively decreases the colonization of C. difficile, probably via alteration of gut microbiota and bile acids. Our probiotics mixture thus offers a promising FMT alternative.